On equitable coloring of corona of wheels - J. Vernold Vivin; K. Kaliraj (Electronic Journal of Graph Theory and Applications (EJGTA), 2016)
The notion of equitable colorability was introduced by Meyer in $1973$ \cite{meyer}. In this paper we obtain interesting results regarding the equitable chromatic number $χ_{=}$ for the corona graph of a simple graph with a wheel graph $G° W_n$. Some extensions into $l$-corona products are also determined.